Proton motive force generated by microbial rhodopsin promotes extracellular electron transfer - Wenqi Ding; Tong Lin; Yun Yang; Wen-Wei Li; Shaoan Cheng; Hao Song (Synthetic and Systems Biotechnology)
The primary limitation to the practicability of electroactive microorganisms in bioelectrochemical systems lies in their low extracellular electron transfer (EET) efficiency. The proton motive force (PMF) represents the electrochemical gradient of protons generated by electron transport and proton pumping across the cytoplasmic membrane, serving as a crucial energy transfer pathway in bacterial membranes. Nevertheless, the impact of PMF on the EET efficiency remains ambiguous, while the microbial rhodopsin offers a simple and efficient avenue for non-photosynthetic cells to harness PMF. Here, we studied the function of three microbial rhodopsins (Arch, Mac, and cR-1) in facilitating EET via their heterologous expression in S. oneidensis, a model electroactive microorganism. Among these, the recombinant strain expressing rhodopsin cR-1 exhibited the highest output power density of 0.87 W/m2, 3.49-fold increase over the wild-type S. oneidensis MR-1. Our further transcriptomics analyses of the energy and materials metabolism of strain cR-1 showed that the underlying mechanism of enhanced EET efficiency was resulted from heterologous expression of the light-driven proton pump. The results suggested that strain cR-1 effectively expels protons to generate additional PMF and provide extra ATP supply to the cells, which facilitated lactate uptake and utilization, thus enhancing electrons generation in cells. This augmented intracellular electron pool capacity ultimately resulted in enhancement of EET rate and power generation efficiency of the recombinant S. oneidensis.